THIRD PARTY LEGAL PROTECTION AS A GOOD-INTENTION BUYER OF LAND WHICH IS INDICATED ABANDONED - Agus Haryono Saputro; Fokky Fuad; Suartini Suartini (UNES Law Review, 2023)
The problem studied in this final assignment islegal protection for third parties as buyers with good intentions for indicated abandoned land, so that it is known how the procedures for possession of abandoned indicated land are known, what are the legal consequences for land indicated as abandoned if it is sold by the right holder to a third party, and what is the legal protection for third parties as a willing buyer either on land indicated as abandoned. Based on this research, it was found that the government's authority regarding state rights in carrying out control of abandoned land is the duty and function of the Ministry of Agrarian Affairs and Spatial Planning/Head of the National Land Agency. Land becomes an object of abandoned land tenure if it is deliberately not cultivated, used and utilized in accordance with the purpose of granting the rights obtained. The process of controlling abandoned land is carried out in several stages, including: evaluation of abandoned land, notification, warning of abandoned land, proposal for designation of abandoned land if after the expiration of the third warning period the land remains abandoned, and determination of abandoned land which includes abolition of land rights, termination of law between land rights holders and their land, and affirmation that the land is directly controlled by the state. The legal consequences for third parties who acquire land through buying and selling plots of land that are indicated as abandoned are because there is no prohibition in the implementation of land registration, where the prohibition on legal action only applies to objects that have been proposed to be designated as abandoned land.